Zwischen Selbstinszenierung und Werkinterpretation: Solistinnen und Solisten - Grotjahn, Rebecca (Institutionen und Medien)

Musikedition – auch ohne Noten - Iffland, Joachim; Grotjahn, Rebecca (Edieren: Geisteswissenschaften im digitalen Wandel | Éditer : les sciences humaines en mutation)

Singen – Körper – Medien - Grotjahn, Rebecca (Stimmen – Körper – Medien. Gesang im 20. und 21. Jahrhundert)

Angstkonstruktionen zwischen „sinnvoller Vorsicht und sinnloser Panik“ - Georgi, Christopher (Angstkonstruktionen)

Biografie und Werk: Henzes „Bassariden“ - Tumat, Antje (Musik und Homosexualitäten. Tagungsbericht Musikwissenschaftliche Homosexualitätenforschung, Bremen 2017 und 2018)

Digitally Assessing Text Comprehension in Grades 3-4: Test Development and Validation - Seifert, Susanne; Paleczek, Lisa (Electronic Journal of e-Learning)
A prerequisite for child reading support at school is adequate assessment. Embedding (repeated) assessment into daily teaching routine is often challenging for teachers in terms of time and organization. The use of digital tools can help teachers in the assessment process (in preparation, evaluation, documentation, etc.). A digital assessment tool (Graz Reading Comprehension test: GraLeV), focusing on assessing reading comprehension skills in Grades 3 and 4 is currently being developed in Austria. This reading assessment covers reading comprehension at the word, sentence, and text level. Text level is assessed via two subtests (Subtest I: presentation of nonsense-stories and corresponding questions, and Subtest II: maze selection). The other levels consist of one subtest each. This paper focusses on the subtests at text level. More specifically, the paper reports the results of two studies. Study 1 describes the development phases and the first piloting of these two subtests (data collection: 10/2019-12/2019). Testing 273 students with preliminary versions of the subtests (Subtest I: 30 items, Subtest II: 60 items) produced information on (a) item difficulty, (b) item discriminatory power, and (c) time limits for future speed testing. Items not meeting the required quality criteria were excluded. The final version of Subtest I consists of 16 questions referring to eight different, short, nonsense-texts. Its testing time (without instructions) is three minutes. The final version of the Subtest II consists of 2 texts each with 15 maze selections (30 items) and testing time is 100 seconds. The internal consistency is found to be good for Subtest I (α=.87) and Subtest II (α=.78 to .80). Study 2 reports on testing for validity and retest-reliability (data collection: 09/2020-11/2020). Student scores in another reading comprehension test, together with teacher assessments of reading comprehension, were used to assess congruent validity. Divergent validity was assessed using teacher assessments of mathematical and socio-emotional skills. As expected, the correlations with the congruent measures were higher than those with the divergent measures. A subsample was tested twice with the GraLeV. Retest-reliability was acceptable for Subtest II. However, the scores obtained at time 2 were higher compared to those at time 1 in both subtests. This is probably the result of increased student familiarity with the digital device and the digital test environment at time 2. The results are discussed in the light of teachers’ needs for standardized digital assessments in order to facilitate the tailoring of student reading support.
Keywords: Computer Science Applications; Education

Is Reading Comprehension Taken for Granted? An Analysis of Austrian Textbooks in Fourth and Sixth Grade - Seifert, Susanne (Technology, Knowledge and Learning)
Abstract The range of teaching materials now available is becoming increasingly diverse. Despite this, however, the use and influence of textbooks in teaching still remains very high. When instructing reading comprehension, teachers often use textbooks as the basis for teaching in language lessons. Establishing a good match between textbooks and the skills to be acquired is therefore essential. In this paper, I investigate whether textbooks used in Austrian schools can adequately support the teaching of reading comprehension skills. Since reading comprehension is the basis for acquiring knowledge in all subjects, science textbooks are examined in addition to (German) language lesson textbooks. Thus, the content pages of four language textbooks and four science textbooks for fourth and sixth grade were analysed in terms of five different categories, i.e. general structural setup, learning goals, text types, text structures, and activities. The results reveal clear variations with respect to learning goals in language textbooks. For example, the extent to which reading comprehension is addressed ranges from 13.64 to 69.70%, depending on the book used. Although not addressed as a learning goal in the science textbooks, reading comprehension is often presupposed, especially in sixth grade. While the instruction of reading comprehension ought to entail coverage of reading strategies, this is often neglected, or only dealt with indirectly. Given the diversity of textbooks analysed, it seems all the more important to stress that teachers should: 1) clarify the goals and teaching strategies of a book before using it, 2) become aware of strategies that support the development of students' reading comprehension, and 3) use textbooks as a complementary (and not sole) tool to support reading comprehension in all subjects.
Keywords: Computer Science Applications; Human-Computer Interaction; Education; Mathematics (miscellaneous)

The presence of students identified as having special needs as a moderating effect on their classmates’ reading comprehension scores in relation to other major class composition effects - Krammer, Mathias; Seifert, Susanne; Gasteiger-Klicpera, Barbara (Educational Studies)
Keywords: Education

Comparing digital to print assessment of receptive vocabulary with GraWo‐KiGa in Austrian kindergarten - Paleczek, Lisa; Seifert, Susanne; Schöfl, Martin (British Journal of Educational Technology)
Keywords: Education

Teaching and learning in a multilingual Europe: findings from a cross-European study - Dockrell, J. E.; Papadopoulos, T. C.; Mifsud, C. L.; Bourke, L.; Vilageliu, O.; Bešić, E.; Seifert, Susanne; Gasteiger-Klicpera, B.; Ralli, A.; Dimakos, I.; Karpava, S.; Martins, M.; et al. (European Journal of Psychology of Education)
Abstract School classrooms within the EU are multilingual learning environments. The diversity of pupils in classrooms raises significant challenges for teachers, but to date, there are no data from large-scale surveys that compare views within and across European countries. A bespoke questionnaire was designed to examine views of current classroom learning environments with respect to the multilingualism. The questionnaire was piloted and subsequently completed by 2792 teachers across different European countries. Eleven countries provided sufficient data for analyses. Results from structural equation modelling showed that teachers’ attitudes could be reliably measured across Europe with the use of carefully devised questionnaire, whose loading and factor structure remained invariant across countries. Teachers’ views about multilingualism were most challenged by the numbers of children in their classes, not the percentage of multilingual pupils in the class. Countries differed in how they perceived multilingualism, with their differences leading to distinctive country clusters. Gender and education level (elementary vs. secondary) differences were also observed irrespective of country. These findings enhance our understanding of the role that the characteristics of teachers and their classrooms play in a multilingual setting across diverse European settings. The practical relevance of the results and new opportunities for teacher training are discussed.
Keywords: Developmental and Educational Psychology; Education

Die Bedeutung affektiver Merkmale beim Mathematiklernen - Rach, Stefanie; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2021 vom GDM-Monat 2021 der Gesellschaft für Didaktik der Mathematik (GDM) (1.-25. März 2021))

Increasing the effect of a remedial mathematics course by switching to an online format during the COVID-19 crisis: evidence from a German university - Büchele, Stefan; Liebendörfer, Michael; Lankeit, Elisa (Teaching Mathematics and its Applications: An International Journal of the IMA)
Abstract Due to the COVID-19 crisis, many courses have been offered digitally. Using data from n = 1,173 business students participating in a preparatory mathematics course at a German university that covered the same content as in 2018, 2019 and 2020, we examine how students’ participation and the effect of the preparatory course changed. The data show that the participation rate has fallen slightly, but students’ participation is rather similar to preceding years. Interestingly, students have participated more intensively. There are clear signs of dishonesty in the self-test (use of a calculator) and significant changes in predictors of performance. In particular, the effect of students’ engagement in the course on their performance substantially increased. Further, we found a gender gap in performance affecting women. Finally, the data show that digital courses can be as effective as on-campus courses.
Keywords: Education; General Mathematics

Gymnasiales Lehramt Mathematik studieren – eine Übersicht zur Studienorganisation in Deutschland - Gildehaus, Lara; Göller, Robin; Liebendörfer, Michael (Mitteilungen der Gesellschaft für Didaktik der Mathematik)
Das gymnasiale Lehramtsstudium der Mathematik ist an deutschen Universitäten unterschiedlich organisiert. Traditionell wurden am Studienbeginn die Fachvorlesungen zur Analysis und Linearen Algebra gemeinsam mit Fachstudierenden gehört. In jüngerer Zeit verbreiten sich alternative Modelle z. B. mit Brückenvorlesungen, die oft spezifisch für das Gymnasiallehramt angeboten werden. Sie können gemeinsame Veranstaltungen mit Fachstudierenden ergänzen oder ersetzen. Dieser Beitrag zeigt auf, welche Modelle wie häufig verbreitet sind, und spricht an, welche hochschuldidaktischen Fragen an der Studiengestaltung hängen.

Mathematisierung als Herausforderung für die politische Bildung - Vajen, Bastian; Gildehaus, Lara; Liebendörfer, Michael; Wolf, Christoph (Schriftenreihe der DVPB. Standortbestimmung Politische Bildung: Gesellschaftspolitische Herausforderungen, Zivilgesellschaft und das vermeintliche Neutralitätsgebot)

Prüfungsformate als Ansatzpunkt gendersensibler universitärer Lehre im Fach Mathematik - Göller, Robin; Gildehaus, Lara; Liebendörfer, Michael; Steuding, Jörn (Mathematik und Gender: Berichte und Beiträge des Arbeitskreise Frauen und Mathematik)

Genese und Funktionen von Lerngruppen in der Studieneingangsphase - Haak, Inka; Gildehaus, Lara; Liebendörfer, Michael (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch?)

University students’ fully digital study of mathematics: an identification of student-groups via their resources usage and a characterization by personal and affective characteristics - Kempen, Leander; Liebendörfer, Michael (Teaching Mathematics and its Applications: An International Journal of the IMA)
Abstract We investigated university students’ study of mathematics in the digital setting context of the COVID-19 pandemic. We gathered data from a survey of 89 students enrolled in a ‘Linear Algebra 1’ course including affective variables, learning strategies, social relatedness and resources considered useful. The results indicate students’ high effort and self-regulation and a high variation in affective characteristics and social relatedness. All the traditional aspects of mathematics teaching (lecture, tutorials and lecture notes) were rated as particularly useful. In addition, the videos from external resources were rated as equally useful as the teaching team’s videos. In contrast, traditional literature such as textbooks was rarely considered useful. The most useful resource rated was communication with peers, underlining the important role of social learning despite fully digital learning environments. Finally, a cluster analysis based on students’ rated usefulness of the resources led to three different user-types. Whereas the ‘digitals’ find the external digital resources very useful (videos, webpages, etc.), the ‘traditionalists’ rate the digitalized traditional resources best (lecture, tutorials, etc.). All resources receive uniformly good ratings from a third group (‘all resource users’). We reflect on our findings in light of the pandemic and describe directions for future research.
Keywords: Education; General Mathematics

The Mathematical Beliefs and Interest Development of Pre-Service Primary Teachers - Liebendörfer, Michael; Hochmuth, Reinhard; Rode, Jana; Schukajlow, Stanislaw (Interim Proceedings of the 44th Conference of the International Group for the Psychology of Mathematics Education)

Was bewirkt die Pflichtabgabe von Übungsaufgaben in der Hochschulmathematik? – Ein empirischer Vergleich - Krapf, Regula; Liebendörfer, Michael (mathematica didactica)
Keywords: Extrinsische Motivation

Artificial Intelligence in the Age of Technoscience - Weber, Jutta (Routledge Social Science Handbook of Artificial Intelligence)

Fortbildung to go: Twitter als Ratgeber für Lehrkräfte - Vochatzer, Stefanie; Schröder, Sarah; Fischer, Christian
Keywords: Lehren Digitale Medien Bildungsforschung Weiterbildung Lehrkraft Social Media Förderung

Caroline Rudolphis „Gemälde weiblicher Erziehung“. Einblicke in die Mädchenerziehung der Spätaufklärung - Vochatzer, Stefanie (POSITIONEN)

Festigkeitssteigerung von Aluminiumblechformteilen der 5000-Serie durch Erweiterung der Formgebungsgrenzen stark kaltverfestigter Ausgangswerkstoffe - Camberg, Alan Adam
Leichtmetalle mit einem breiten Eigenschaftsspektrum gewährleisten die Realisierung ressourcenschonender Produkte und ermöglichen die Intensivierung sortenreiner Kreislaufwirtschaften. Die vorliegende Arbeit untersucht einen wärmeunterstützten Ansatz zur Erhöhung der Formgebungsgrenzen stark kaltverfestigter AlMg4,5 Blechwerkstoffe bei gleichzeitiger Beschränkung des Festigkeitsverlustes durch Erholungseffekte. Experimentelle Untersuchungen stellen eine wissenschaftlich fundierte Erkenntnisbasis über die werkstofftechnischen Wirkzusammenhänge des untersuchten Prozesses dar. Gepaart mit an realen Bauteilgeometrien validierten numerischen Simulationsmodellen legt diese Arbeit einen methodischen Grundstein für die industrielle Umsetzung des hier untersuchten Blechumformprozesses. Die erzielte mittlere Dehngrenze des exemplarisch untersuchten Bauteils übersteigt die Dehngrenze eines konventionellen AlMg4,5 Werkstoffes um 190 %. Mit 320 MPa entspricht sie dem Festigkeitsniveau des walzharten Blechhalbzeuges im Lieferzustand, ein Wert, der nach dem aktuellen Stand der Technik auf Bauteilebene ausschließlich mit aushärtbaren AlMgSi Legierungen darstellbar ist.
Keywords: Aluminium; Blechumformung; AlMg; Materialmodellierung; Duktiles Versagen; Halbwarmumformung; Automobil; Leichtbau; Uni-Alloy; 5000-Serie; 5182; GISSMO

Beitrag zur Reduzierung der Fehlerhäufigkeit bei der Online-Lackierung von SMC-Außenhautbauteilen - Huber, Johannes
Der Verbau von Sheet Moulding Compounds im automobilen Außenhautbereich führt in der industriellen Praxis regelmäßig zu abnehmenden Direktläuferquoten in der Technologie Oberfläche, denn neben bekannten Lackierfehlern ergeben sich auch werkstoff-spezifische Oberflächendefekte, welche einen Bauteilwechsel bedingen. Die hier vorliegende Arbeit soll einen aktiven Beitrag zur Reduzierung von Ausschuss und Nacharbeit entlang der Lackierprozesskette leisten. Zu Beginn werden die erfolgskritischen Oberflächendefekte identifiziert und die zugehörigen Fehlerursachen ermittelt, ehe anschließend die Entwicklung der Fehlstellengrößen in Folge der Temperaturbelastung während der Trocknerdurchfahrten untersucht wird. Ferner soll die Auswirkung einer zusätzlich applizierten Oberflächengrundierung auf die Fehlerhäufigkeit sowie die Oberflächengüte im decklackierten Zustand geprüft werden. Als weitere Möglichkeit zur Problemlösung wird eine in den Prozessablauf integrierte Qualitätskontrolle gesehen, weshalb in dieser Arbeit ebenso die Eignung bekannter zerstörungsfreier Prüfmethoden für die präventive Fehlererkennung überprüft und ein zweistufiges Prüfkonzept erarbeitet wird. Das Aufzeigen möglicher Handlungsalternativen sowie die kostentechnische Gegenüberstellung der verschiedenen Anbauvarianten runden die Arbeit ab.
Keywords: Sheet Moulding Compounds; SMC; Online-Lackierung

Konzeptionierung und Auslegung eines Vorderachsträgers in hybrider Leichtbauweise im C-Segment - Pöhler, Simon
Im Rahmen dieser Arbeit wurde ein neuartiger Achsträger in hybrider Bauweise entwickelt und untersucht. Dieser besteht aus einer metallischen Oberschalenstruktur und einer mit Rippen ausgeformten glasfaserverstärkten thermoplastischen Unterschale (GMT), welche zur Einstellung der optimalen Steifigkeit dient. Die Rippen und Unterschale werden hierzu in einem Fließpressverfahren entweder gemeinsam als ein Bauteil oder als separate Einzelteile hergestellt. Durch den lokalen Einsatz von Faserverbundwerkstoffen in der Unterschale und der Rippenstruktur wird ein signifikanter Gewichtsvorteil gegenüber einer Referenzstruktur aus Stahl erzielt. Durch die Verwendung des GMT-Unterbodenschutzes konnten zudem die akustischen Eigenschaften des Fahrwerks hinsichtlich der Dämpfung positiv beeinflusst werden. Die hohen Anforderungen bzgl. Steifigkeit, Festigkeit und Beständigkeit der sicherheitsrelevanten Fahrwerkskomponente konnten unter Einhaltung des Bauraums erfüllt werden. Gleichzeitig konnte das Gesamtgewicht der Komponente im Vergleich zur klassischen Referenzstruktur um 30 % reduziert werden.
Keywords: hybrider Achsträger; Leichtbau; Hybridsysteme

Kooperativ Forschen(d) lernen im inklusiven Sachunterricht der Primarstufe – Ein Theorie-Praxis verzahnter Ansatz zur Vorbereitung von Sachunterrichtsstudierenden auf das Praxissemester - Kirsch, Alexander; Blumberg, Eva; Hellmich, Frank; Hoya, Fabian Karl (Theorie und Praxis in der Lehrerbildung. Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)

Effects of teacher feedback on children’s self-concepts and motivation in science lessons. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

The role of teacher feedback for children’s self-concepts and motivation in primary school science lessons. Single Paper. ECER 2021 (European Conference on Educational Research). “Education and Society: expectations, prescriptions, reconciliations” - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Ansatz zur Beschreibung von unregelmäßig gefügten Kunststofffilamenten aus Thermoplasten in Wirrmattenstrukturen unter mechanischer Belastung zur Substitution von Schaumstoffen in Polstern und Matratzen - Westhues, Tobias Thomas

Beitrag zur verfahrenstechnischen Entwicklung der Direktcompoundierung im Spritzgießprozess mit sequentiell arbeitenden Kolbenspritzeinheiten - Wittke, Marius

Untersuchung und Prävention der Alterung von Silikon-Gießwerkzeugen beim Polyurethan-Vakuumgießen - Wortmann, Martin

Beiträge zur verfahrenstechnischen Entwicklung der Spritzgießdirektcompoundierung (SGDC) - Jilg, Jannik Richard

Nicht-isotherme Druck-Durchsatzberechnung von Kautschukextrudern - Stüker, Daniel

Global weak solutions in a three-dimensional Keller-Segel-Navier-Stokes system with gradient-dependent flux limitation. - Winkler, Michael (Nonlinear Analysis: Real World Applications)

Suppressing blow-up by gradient-dependent flux limitation in a planar Keller-Segel-Navier-Stokes system. - Winkler, Michael (Zeitschrift für Angewandte Mathematik und Physik)

Can rotational fluxes impede the tendency toward spatial homogeneity in nutrient taxis (-Stokes) systems? - Winkler, Michael (International Mathematics Research Notices)

Boundedness in a three-dimensional Keller-Segel-Stokes system with subcritical sensitivity. - Winkler, Michael (Applied Mathematics Letters)

Does spatial homogeneity ultimately prevail in nutrient taxis systems? A paradigm for structure support by rapid diffusion decay in an autonomous parabolic flow. - Winkler, Michael (Transactions of the American Mathematical Society)

Quo Vadis Conferences in the Business and Information Systems Engineering (BISE) Community After Covid - Leimeister, Jan Marco; Stieglitz, Stefan; Matzner, Martin; Kundisch, Dennis; Flath, Christoph; Röglinger, Maximilian

Influence of pin geometry on the joint strength of CFRT-metal hybrid parts with metallic pins - Popp, Julian; Kleffel, Tobias; Drummer, Dietmar (Joining Plastics)

Energy Efficiency Technologies in Germany - Meschede, Henning

Energie einsparen in Industrie und Gewerbe - Schlosser, Florian; Hechelmann, Ron-Hendrik; Meschede, Henning; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Mit Energieeffizienz Grundlagen legen - Hechelmann, Ron-Hendrik; Schlosser, Florian; Meschede, Henning; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Wer grüne Energie will, muss auch koppeln und speichern - Meschede, Henning; Khripko, Diana; Schlüter, Alexander (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Energienachfrage flexibler gestalten - Khripko, Diana; Meschede, Henning; Meschede, Eva (Das Energiesystem der Zukunft in Smart Cities und Smart Rural Areas)

Review of infrared spectroscopy techniques for the determination of internal structure in thin SiO2 films - de los Arcos de Pedro, Maria Teresa; Müller, Hendrik; Wang, Fuzeng; Damerla, Varun Raj; Hoppe, Christian; Weinberger, Christian; Tiemann, Michael; Grundmeier, Guido (Vibrational Spectroscopy)

Design of a TiAlON multilayer coating: Oxidation stability and deformation behavior - Bobzin, K.; Kalscheuer, C.; Grundmeier, G.; de los Arcos de Pedro, Maria Teresa; Schwiderek, S.; Carlet, M. (Surface and Coatings Technology)

Produktspezifische Optimierung der Nachhaltigkeit im Ersatzteilmanagement. Ganzheitliche Vorgehensweise zur Bewertung der Nachhaltigkeit additiv gefertigter Komponenten für den Aftermarket - Gräßler, Iris; Hillebrand, Stefan; Thiele, Henrik (Digitalisierung im Kontext von Nachhaltigkeit und Klimawandel)

Moderne Heldin im antiken Gewand? Anne Webers „Annette, ein Heldinnenepos“ - Süwolto, Leonie

In situ backside Raman spectroscopy of zinc oxide nanorods in an atmospheric‐pressure dielectric barrier discharge plasma - Knust, Steffen; Ruhm, Lukas; Kuhlmann, Andreas; Meinderink, Dennis; Bürger, Julius; Lindner, Jörg K. N.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Journal of Raman Spectroscopy)